Heavy Metal Toxicity in Human Health: Mechanisms, Impacts, and Mitigation Strategies - Muhammad Muneeb Hassan; Dr. Adeel Hussain Chughtai; Mujahed Ali; Iqra Yasin; Ubaid Ur Rehman; Kainat Haider; Haseeb Ullah; Seema Batool; Muhammad Abdullah, (Dialogue Social Science Review (DSSR), 2024)
Heavy metals such as lead, mercury, cadmium, and arsenic are naturally occurring elements that can become toxic at low concentrations and pose significant health risks to humans and the environment. Their accumulation in the body can lead to severe health conditions, including neurological disorders, cancer, kidney damage, and reproductive issues. The sources of heavy metal contamination include industrial processes, agricultural activities, and environmental pollution, all of which contribute to their presence in food, water, and air. The mechanisms of toxicity often involve oxidative stress, DNA damage, and disruption of critical cellular functions. Vulnerable populations, such as children and pregnant women, are at higher risk due to the adverse effects these metals have on development and health. Addressing the health impacts of heavy metals requires a comprehensive approach, including dietary strategies, detoxification agents, chelation therapy, and effective public health initiatives. Preventive measures, such as reducing exposure through regulatory policies, raising public awareness, and improving safety standards in occupational settings, are essential to mitigate the long-term effects of heavy metal toxicity. This review explores the sources, mechanisms, health impacts, and mitigation strategies for heavy metal toxicity, highlighting the need for continued research and public health interventions to reduce the global burden of heavy metal exposure.